Dendritic cells and aging: consequences for autoimmunity. (January 2012) - Agrawal, Anshu; Sridharan, Aishwarya; Prakash, Sangeetha; Agrawal, Harsh
The immune system has evolved to mount immune responses against foreign pathogens and to remain silent against self-antigens. A balance between immunity and tolerance is required as any disturbance may result in chronic inflammation or autoimmunity. Dendritic cells (DCs) actively participate in maintaining this balance. Under steady-state conditions, DCs remain in an immature state and do not mount an immune response against circulating self-antigens in the periphery, which maintains a state of tolerance. By contrast, foreign antigens result in DC maturation and DC-induced T-cell activation. Inappropriate maturation of DCs due to infections or tissue injury may cause alterations in the balance between the tolerogenic and immunogenic functions of DCs and instigate the development of autoimmune diseases. This article provides an overview of the effects of advancing age on DC functions and their implications in autoimmunity.